Fabrication of a lithium-ion battery separator from cellulose acetate of empty palm fruit bunches with the addition of PVDF - Rismadani Haryanti; Romi Fadli Syahputra; Delovita Ginting (Indonesian Physics Communication, 2024)
The separator is a crucial element in lithium-ion batteries that is positioned between the anode and cathode. Its primary function is to prevent direct contact between the electrodes, hence avoiding electrical short circuits. Lithium ion battery separators are typically composed of polyvinylidene fluoride (PVDF) and polyacrylonitrile (PAN) polymers, which possess excellent ionic conductivity and mechanical qualities. Nevertheless, these polymers and materials possess numerous drawbacks, necessitating adjustments for their further development. The objective of this study is to examine the impact of incorporating novel polymers into the constituents of the separator. The alteration utilises a novel polymer called cellulose, specifically the cellulose derivative known as cellulose acetate. The cellulose acetate utilised is derived from the empty fruit bunches of oil palm trees. Cellulose acetate offers several benefits, including affordability, the ability to selectively adsorb substances, solubility in a wide range of solvents (particularly organic solvents), hydrophilicity, and its origin from renewable sources. The separator was fabricated using the reflux process, which involved mixing 5.6 g of PVDF and 0.7 g of Al(OH)3 with varying amounts of CA (0.1 g, 0.2 g, and 0.3 g). The conducted tests include the thickness test, elongation test, and PSA test. According to the test results, the separator is viable and complies with the standards.